2009
DOI: 10.1016/j.str.2008.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Biochemical Studies on Procaspase-8: New Insights on Initiator Caspase Activation

Abstract: Caspases are proteases with an active-site cysteine and aspartate specificity in their substrates. They are involved in apoptotic cell death and inflammation, and dysfunction of these enzymes is directly linked to a variety of diseases. Caspase-8 initiates an apoptotic pathway triggered by external stimuli. It was previously characterized in its active inhibitor bound state by crystallography. Here we present the solution structure of the monomeric unprocessed catalytic domain of the caspase-8 zymogen, procasp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(113 citation statements)
references
References 54 publications
(73 reference statements)
6
105
0
1
Order By: Relevance
“…This assumption was motivated by structural considerations. Namely, procaspase-8 homodimers or procaspase-8/c-FLIP L heterodimers form hydrogen bonds between the catalytic subunits, 28,33 which are lacking in the short isoforms of c-FLIP as well as in the procaspase-8 prodomain.…”
Section: Resultsmentioning
confidence: 99%
“…This assumption was motivated by structural considerations. Namely, procaspase-8 homodimers or procaspase-8/c-FLIP L heterodimers form hydrogen bonds between the catalytic subunits, 28,33 which are lacking in the short isoforms of c-FLIP as well as in the procaspase-8 prodomain.…”
Section: Resultsmentioning
confidence: 99%
“…Since dimerization is a precondition for self-processing and caspase-8 activity [66], we speculated that HSV-2 R1 could interact with caspase-8 in a way that inhibits this event. Supporting our hypothesis, we found that HSV-2 R1 protects cells against apoptosis induced by over-expression of GFP-tagged caspase-8 that is known to be triggered by dimerization/activation of the over-expressed zymogen [51].…”
Section: Discussionmentioning
confidence: 99%
“…36,37 In contrast, the IL of the procaspase-8 monomer interacts with active site loop 1 and prevents productive active site formation. 17 In addition to the structural features of the IL and pro-domain regions, the dimer interfaces are very different between caspases-3 and -8. While the interface of caspase-3 contains several backbone hydrogen bond interactions below 3 Å , caspase-8 contains few hydrogen bonds, and the interactions are at longer distances (>3 Å , Fig.…”
Section: Discussionmentioning
confidence: 99%
“…15 The structure of uncleaved procaspase-8 shows that activation occurs through the rearrangement of surface loops that form the substrate-binding cleft, which properly orients the catalytic residues. 17 In addition to homodimerization, procaspase-8 also forms heterodimers with the structurally similar protein, FLIP. [18][19][20] In the cell, the heterodimer inactivates RIPK1, preventing necroptosis and promoting cell survival, and it is thought that heterodimerization represents the default cellular pathway.…”
Section: Introductionmentioning
confidence: 99%